12-week curcumin supplementation may relieve postexercise muscle fatigue in adolescent athletes - Bai, Kai-Yuan; Liu, Gin-Hua; Fan, Chun-Hao; Kuo, Liang-Tseng; Hsu, Wei-Hsiu; Yu, Pei-An; Chen, Chi-Lung (Frontiers in Nutrition, 2023)
High-intensity exercise causes oxidative stress, muscle soreness, and muscle fatigue, leading to reduced exercise performance. Curcumin possesses antioxidative and anti-inflammatory properties and thus alleviates postexercise damage. Therefore, this study evaluated the effect of curcumin on athletes’ postexercise recovery. A non-randomized prospective cohort investigation was done. We recruited middle and high school athletes engaged in wrestling, soccer, and soft tennis. During the 12-week daily exercise training, the participants were assigned to receive curcumin supplementation (curcumin group) or not (control group). Body composition, exercise performance, inflammatory factors, muscle fatigue, and muscle soreness were recorded at the baseline and end of the study. We used the Mann–Whitney U test to compare the participants’ demographics, such as age, height, weight, and training years. The Wilcoxon test was used to compare the differences between the groups before and after curcumin supplementation. Of 28 participants (21 men and 7 women, with a mean age of 17 years), 13 were in the curcumin group and 15 in the control group. A significant decrease in muscle fatigue and muscle soreness scores was observed in the curcumin group after 12 weeks. Moreover, a significant decrease in the 8-hydroxy-2 deoxyguanosine level and a significant increase in basic metabolic rate and fat-free mass were observed in the curcumin group. In conclusion, curcumin can reduce muscle fatigue and soreness after exercise, indicating its potential to alleviate postexercise damage. It could be considered to cooperate with nutritional supplements in regular training in adolescent athletes.